SIMULASI KENDALI JARAK JAUH BERBASIS WEB - Priatna, Edvin (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2010)
Control of household electrical equipment is not only expected to be done at the time were in the house, but at the outside of the equipment is expected be monitored and controlled remotely. To overcome this, so here tried to do a simulation to determine the condition and also manually control remotely electrical load. Control system used is by using a web-based client server, the exchange of data in the internet network to a web client program, which serves submit requests via the HTTP GET method or POST, while the program is functioning as a web server waiting for requests and serves to transmit the web to web data request. The results of testing control systems tested on local networks, electrical load can be controlled manually via the button directly and via the browser and the electric load condition changes due to manual control can be monitoring from the browser.